The role of miR-7 as a potential switch in the mouse hypothalamus-pituitary-ovary axis through regulation of gonadotropins. (1st December 2020) - He, Jing; Xu, Shirong; Ji, Zengjun; Sun, Youhong; Cai, Bingyan; Zhang, Shanhui; Wang, Pingping
Abstract: The hypothalamus-pituitary-ovary (HPO) axis plays fundamental roles in female neuroendocrinology and reproduction. Pituitary gonadotropins are located in the center of this axis. Previous investigation suggested that miR-7 is closely linked with gonadotropins. However, the interaction between miR-7 and the HPO axis remains unclear. This study aims to determine whether and how miR-7 functions in this axis. A mouse ovariectomy model and mouse primary pituitary cells were used in this study. The results showed that miR-7 is localized to gonadotrophs and somatotrophs. miR-7 can inhibit the expression, synthesis and secretion of gonadotropins, but not growth hormones. Gonadotropin-releasing hormone (GnRH) has inhibitory effects on miR-7, while estrogen enhances miR-7 expression. miR-7 is vital for the pathway by which GnRH and estrogen regulate gonadotropins by targeting v-raf-leukemia viral oncogene 1 ( Raf1 ). Together, these results indicate that miR-7 acts as a potential switch in the feedback loop of the HPO axis by regulating gonadotropins. Highlights: MiR-7 inhibits gonadotropin expression, synthesis and secretion. GnRH has inhibitory effects on miR-7 and estrogen has promoting effects on miR-7. MiR-7 is vital in the pathway of GnRH and estrogen regulating gonadotropins. MiR-7 is a potential molecular switch in HPO axis by targeting Raf1 .